Reviewing the sports coach mentoring literature: a look back to take a step forward - Leeder, T. M.; Sawiuk, R. (Sports Coaching Review, 2021)
This article takes a look back, in order to take a step forward, for sports coach mentorship within both academia and practice. Consequently, this article aims to review the contemporary trends within the sports coach mentoring literature and beyond to build upon earlier foundations. Throughout, four areas of significance are identified: (1) A sociocultural analysis of sports coach mentorship; (2) multiple-mentors and developmental networks; (3) developing sports coach mentors; and (4) gender and role models. The existing literature within each area is introduced, analysed, and critiqued, before an innovative future research agenda is established. Whilst mentorship is regularly utilised within sports coaching, the practice remains undertheorised and conceptually vague. Therefore, this literature review attempts to reconstruct sports coach mentorship by highlighting gaps in our knowledge and instigating innovative research agendas to produce contextually and culturally bound empirical evidence. Thus, this article advances our understanding of mentoring practice within sports coaching.